(untitled) (Journal of Tourism and Hospitality Education, 2021)
The hospitality and tourism sector is considered the backbone for economicgrowth, especially in developing countries. However, this thriving sector is particularly vulnerable to naturaland human-made disasters. This study assesses the impact of the COVID-19 (coronavirus disease-2019) pandemic in India’s hospitality and tourism sector by addressing essential aspects such as current conditions and challenges as well as future perspectives. The secondary research methodology has been applied for the research. For data collection, the secondary data has been collected through literature, journal articles, government documents, etc. The research findings show that COVID-19 in India has significantly affected the hospitality and tourism sector. Global and domestic tourists have canceled their programs to visit the natural, historical, religious, and cultural sites. The flight tickets and the hotel reservations have been canceled. A significant number of workers in the sector have lost their jobs. This pandemic has affected the economy of the country as well as the well-being of the individuals to a large extent. As the intensification of the COVID-19 is being thought to cause a long-term impact, this study could be relevant to the decision-makers in regards to the crucial task of reviving the sector.